SOSIALISASI DAMPAK NEGATIF GADGET TERHADAP KEHIDUPAN ROHANI ANAK DUSUN PAYOK DESA LAMOANAK KECAMATAN MENJALIN - Yenti Krisdayanti Gulo; Nervin Zalukhu; Silsi Nadiati Saogo (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2022)
Technological developments cannot be avoided by humans but must be followed. One that is very familiar in society is gadgets. A gadget is an object that anyone in carrying out their activities needs. It is not only adults who use gadgets; children also know how to operate gadgets well. Gadgets are very useful for anyone who use them, but they will have a good impact if users can be controlled properly, especially in the spiritual development of children. Payok Hamlet, Lamoanak Village, Menjalin District, Landak District, and West Kalimantan were the research locus. The method used in this research is a survey method, in which researchers go directly to the field to make observations. After making new observations, communication and outreach to the community were carried out. The negative impact of gadgets on children’s spiritual growth has begun to be felt by children in this hamlet. Oneway parents can so that their children are not too dependent on gadgets is that parents must have much time with their children so that time to use gadgets for the children will be reduced the negative impact of gadgets can be avoided as much as possible.